Preparation of Paralympic athletes; environmental concerns and heat acclimation - Price, M. J. (Frontiers in Physiology, 2016)
High ambient temperature and relative humidity (rh) are of great importance when considering athletic performance. Such factors are of particular interest when considering that the majority of Paralympic Games have been hosted at locations with potentially challenging environmental conditions (e.g., Atlanta, Sydney, Athens, Beijing) and a range of Paralympic athletes exhibit conditions manifesting thermal dysfunction. Prior to the Atlanta Games in 1996, Nielsen (1996) considered the "fight against physics" with respect to high ambient temperature (30-38°C) and relative humidity (rh; 40-80%) on endurance performance for able-bodied athletes. It was noted that with such potentially severe conditions outdoor endurance based performances could be severely reduced, especially in spells of high humidity. Strategies to prevent heat illness were recommended including events being scheduled at times of lower thermal stress or re-scheduled if temperatures were above 35°C. However, how these conditions may affect Paralympic athletes has not yet been reported. This article will consider what is known regarding enhancing (or maintaining) performance in the heat in athletes with motor disabilities in preparation for Rio 2016.